1966
DOI: 10.1136/bmj.1.5503.1576
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Animal Helminths as a Factor in Causing Poliomyelitis and Epilepsy

Abstract: BtRnau contact, or by contaminated objects. According to Jellard (1957), the main reservoirs of this organism are (a) open lesions in the mothers, babies, or staff ; (b) adult skin and nasal carriers; and (c) the babies themselves, the umbilical cord being one of the principal sites. More than 80% of hospital-born infants are said to develop umbilical colonization by staphylococci at the fourth day (Fairchild, Graber, Vogel, and Ingersoll, 1958). In this respect the presence of the organism in the babies' stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 7 publications
2
38
0
1
Order By: Relevance
“…Such a mechanism is assumed to cause epilepsy. Accordingly, patients with epilepsy are four times more frequently positive for antibodies against T. canis than controls 18 . Similarly, larvae may cause a focal granulomatous reaction when they reach the spinal cord, compromising anterior horn cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Such a mechanism is assumed to cause epilepsy. Accordingly, patients with epilepsy are four times more frequently positive for antibodies against T. canis than controls 18 . Similarly, larvae may cause a focal granulomatous reaction when they reach the spinal cord, compromising anterior horn cells.…”
Section: Discussionmentioning
confidence: 96%
“…To explain a possible causal relation between neurotoxocarosis and LMND in the patient reported, three pathogenetic scenarios can be put forward: First, larvae of T. canis on their migration from the intestines to target tissues carry with them bacteria, viruses, or other infectious agents [16][17][18] . Via this pathway some patients may have been infected with the polio-virus or other agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1964) that in addition to psittacosis, a number of severe illnesses can result from infection through close contact with virus-like organisms excreted in the respiratory and faecal discharges of apparently healthy psittacine birds such as budgerigars. Other observers (Woodruff and Thacker, 1964;Woodruff, Bisseru and Bowe, 1966) have reported that similar intimate contact with dogs can result in human beings becoming infected with virus-carrying larvae which may produce poliomyelitis or result in granulomatous foci which, if occurring in the brain, may give rise to epilepsy. It has been stated (Doll, 1965) that virus-induced cancers have been observed in so many animals that it would be surprising if man were completely immune.…”
Section: Discussionmentioning
confidence: 99%
“…Another unsolved issue is the meaning of the association between toxocara seropositivity and epilepsy consistently reported in literature. Early observations have highlighted a high titers of T. canis antibodies among epileptic subjects [17,18]. After these reports, several casecontrol studies have been carried out in different geographic areas, often supporting this possible positive association between epilepsy and T. canis seropositivity [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 98%